Strain Measurement in Hyrax Appliances Using FBG Sensors in a 3D-Printed Human Maxillary Model - Coimbra, Wagner; Oliveira, Pedro; Theodosiou, Antreas; Marques, Carlos; Kalli, Kyriacos; Leal-Junior, Arnaldo (My University, 2022)
This letter presents a method of measuring the strain during rapid maxillary expansion (RME) using fiber Bragg grating (FBG) sensors. The activation of the central jackscrew of the Hyrax expander provides the forces required to expand the maxilla that are transmitted to the teeth by a metallic wire. The strain resulted from the opening forces was measured by a FBG sensor bonded to the posterior arm of the appliance. A proof of concept is shown using a 3D printed maxillary model of the biomechanical structure of a human maxilla, in which the appliance was mounted. The sensor was able to measure static and dynamic events, such as the strain accumulation and viscoelastic strain patterns. An increase in the strain is observed as the number of activations increases. A fast decrease in the strain between activations was also observed. In spite of using a plastic model with viscoelastic properties, this decrease may be related to limitations of the central jackscrew. The instrumentation of the Hyrax expanders using FBG sensors assists in clinical studies on the biomechanics and the efficiency of RME. Different expanders can be compared using the present sensor, and tests on their components, especially the central jackscrew, contributes to improvements or new procedures on such treatments.
Keywords: Fiber Bragg grating sensors; strain measurement; orthodontic biomechanics; rapid maxillary expansion